Reviewing the impacts of community energy initiatives in New Zealand. (2nd January 2021) - Roberts, Ryan; Brent, Alan; Hinkley, Jim
ABSTRACT: The New Zealand government has earmarked community energy as an investment mechanism that could assist the country in reaching its climate change goals, as well as lead to local benefits for its citizens. The objective of this paper is to identify what community energy initiatives are occurring in New Zealand, and the respective impacts that have arisen. A desk survey was undertaken, through an academic database and internet search to collect relevant resources and data. The country has a history of community energy initiatives; however, data on the impacts of community energy initiatives are scarce, at both a local and national level. The study also found diversity in the communities that are, or possibly could, benefit from community energy projects, each with differing motivations for participation. A national understanding of the successful impacts of community energy initiatives is needed, as well as more monitoring and analysis on the impacts of current projects. Ascertaining the true value of community energy is a complex task, but vital should development of these projects be pursued.